Insolation forcing of coccolithophore productivity in the western tropical Indian Ocean over the last two glacial-interglacial cycles - Tangunan, Deborah; Baumann, Karl-Heinz; Paetzold, Juergen; Henrich, Ruediger; Kucera, Michal; De Pol Holz, Ricardo Hernán; Groeneveld, Jeroen (My University, 2017)
We present a new coccolithophore productivity reconstruction spanning the last 300ka in core GeoB12613-1 retrieved from the western tropical Indian Ocean (IO), an area that mainly derives its warm and oligotrophic surface waters from the eastern IO. Application of a calibrated assemblage-based productivity index indicates a reduction in estimated primary productivity (EPP) from 300ka to the present, with reconstructed EPP values ranging from 91 to 246gC/m(2)/yr. Coccolithophore assemblages and coccolith fraction Sr/Ca indicate three main phases of productivity change, with major changes at 160 and 46ka. The productivity and water-column stratification records show both dominant precession and obliquity periodicities, which appear to control the paleoproductivity in the study area over the last two glacial-interglacial cycles. Shallowing of the thermocline due to strengthening of the trade winds in response to insolation maxima resulted to peaks in EPP. Comparison with the eastern IO productivity and stratification coccolithophore data reveals good correspondence with our records, indicating a strong tropical Pacific influence in our study area. Both of these records show high productivity from 300 to 160ka, interpreted to be due to stronger Walker Circulation while the declining productivity from 160ka to the present day is a consequence of its weakening intensity.
Keywords: coccolithophores: western indian ocean; insolation forcing; equatorial productivity; coccolith sr; ca; quaternary